Desempenho físico e qualidade da movimentação de equinos mangalarga marchador treinados com aparelho de eletroestimulação de corpo inteiro - Bruna Dias Menezes (2021)
Brazil has the fourth largest equine herd in the world, with the Mangalarga Marchador being the most numerous horse breed bred in the country. The marcha contest is the most important functional test performed with this breed and has been characterized as a submaximal intensity exercise. The particularities of the marcha test and the fact that equine athletes present a high incidence of lameness, shows that strategies should be adopted to improve the period of physical conditioning of these animals, in order to preserve their athletic longevity. Electrotherapy has been used in equine medicine as a physiotherapeutic rehabilitation resource and there are no studies on its use in the sports performance of this species. The objective of the research was to test the effects of the use of a device for whole-body electrostimulation on the physical conditioning and quality of movement of Mangalarga Marchador horses. Twelve untrained Mangalarga Marchador mares, from the same breeder, aged between 3 and 4 years, with a mean body score of 3 (scale from 0 to 5) and mean weight of 350 kg, were randomly assigned to groups GA and GB. Both groups were conditioned with the same exercise protocol, but the GB animals were submitted to 30 min sessions of electrostimulation before each work session. The physical performance of the animals was evaluated in four marcha tests, the first one before starting training and the others at 10, 28 and 42 days of training. In the tests, physiological variables (rectal temperature, heart and respiratory rate) and blood (blood count, lactate and creatine kinase and aspartate aminotransferase enzymes) were evaluated. Before and at the end of the training period, the animals were evaluated for gait kinematic variables and qualitative gait parameters. The experimental design was completely randomized in subdivided plots. Data were submitted to three-way ANOVA (treatment x test x moment) for repeated samples (animal), followed by Tukey's test (p≤0.05) or SNK test (p≤0.05). Heart rate at 10 minutes of recovery was lower in GB (p<0.05) at 28 days of training. The marcha time between the first and the last test was higher in GB (p<0.05), and at the end of the experimental period, only GB reached a marcha time of more than 50 min. In the qualitative assessment of gait, the use of electrical stimulation during training (GB) improved the quality of movement and stability of the pelvic limbs. In the kinematic analysis, training increased (p≤0.05) the stride length in both experimental groups and there was an increase in the vertical displacement of the thoracic hooves and a reduction in the vertical displacement of the neck in GA. It was concluded that the use of whole-body electrostimulation associated with 42 days of training improved physical conditioning and the quality of movement and stability of the pelvic limbs of MM horses.